Evaluation Of Swelling – Shrinkage Of Soil Stabilized With Cement and Matos Soil Stabilizer - Saputra, Muhammad Dzulhaj (International Journal of Aviation Science and Engineering - AVIA, 2023)
This study aims to investigate the effect of matos soil stabilizer on soil stabilized with cement. The study utilizes 5% Portland Composite Cement (PCC) ratio by weight of dry soil and matos soil stabilizer at 0%, 1%, 2%, 4%, and 8% by weight of Portland Composite Cement, with curing periods of 0 days, 7 days, and 14 days, focusing on the swelling and shrinkage characteristics. The best result showed in a mixture with a variation of 8% matos soil stabilizer under 14 days curing with a plasticity index 12,227% Swelling (CBR Soaked) 1,423, Swelling Pressure 1,469 kg/cm2 and free swelling index 16,667%. The test results indicate that the mixtures with varying amounts of matos soil stabilizer in the cement-treated soil with different curing periods can reduce soil swelling, as observed from the values of plasticity index, Swelling (soaked CBR (California Bearing Ratio)), swelling pressure, and free swelling index, which decrease progressively. Therefore, it can be concluded that increasing the amount of matos soil stabilizer and prolonging the curing time can reduce the swelling and shrinkage characteristics of the soil.